Bimetal / carbon nanotube compound modified glassy carbon electrode and preparation method and application thereof

By modifying nickel-cobalt bimetallic nanoparticles and multi-wall carbon nanotube composites on glass carbon electrodes, the problems of low sensitivity and poor stability in the determination of paracetamol are solved, and detection effects of high sensitivity, low detection limit and good stability are achieved.

CN119666952APending Publication Date: 2025-03-21HANGZHOU NORMAL UNIVERSITY

Patent Information

Application Number
CN202411835237.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-13
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing composite glass carbon electrodes have low sensitivity, high detection limit and poor stability when measuring paracetamol.

Method used

The glass carbon electrode is modified by a bimetal/carbon nanotube composite made of nickel-cobalt bimetallic nanoparticles and multi-wall carbon nanotubes, and the nickel-cobalt bimetallic nanoparticles are deposited by electrochemical deposition to form a composite modified layer.

Benefits of technology

The electrocatalytic activity is improved, the detection performance is enhanced, and the detection effect is achieved with good stability, low detection limit (2μmol/L), high sensitivity and selectivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119666952A_ABST
    Figure CN119666952A_ABST
Patent Text Reader

Abstract

The invention discloses a bimetallic / carbon nanotube compound modified glassy carbon electrode as well as a preparation method and application thereof, and belongs to the technical field of electrochemical analysis. The bimetallic / carbon nanotube compound modified glassy carbon electrode provided by the invention comprises a glassy carbon electrode substrate and a bimetallic / carbon nanotube compound compounded on the glassy carbon electrode substrate, the bimetallic / carbon nanotube compound is prepared from nickel-cobalt bimetallic nanoparticles and a multi-walled carbon nanotube. The prepared bimetallic / carbon nanotube compound modified glassy carbon electrode has excellent electrocatalytic activity, has the advantages of good stability, low detection limit and high sensitivity and selectivity in the process of determining paracetamol, can realize on-site rapid detection of paracetamol, has the advantages of being convenient to carry and simple to operate, and has a wide application prospect. Wide application prospects are realized in medicine safety and clinical medical treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of electrochemical analysis technology, and in particular relates to a glassy carbon electrode modified with a bimetallic / carbon nanotube composite, and a preparation method and application thereof. Background Art

[0002] Paracetamol (PCT), also known as acetaminophen or N-methyl-p-aminophenol, is one of the most widely used over-the-counter drugs in the world, with the effects of reducing fever and relieving pain. However, excessive use can cause adverse consequences such as severe liver damage. Therefore, accurate detection of the content of paracetamol in drugs is of great significance for controlling drug quality and ensuring patient safety.

[0003] At present, the commonly used analytical methods for determining paracetamol mainly include high performance liquid chromatography, flow injection chemiluminescence, spectrophotometry, capillary electrophoresis, fluorescence and electrochemical methods, but these methods have the disadvantages of small detection range, low sensitivity, cumbersome operation, expensive instruments or time-consuming sample processing. Among them, electrochemical analysis has the characteristics of high sensitivity, fast analysis speed, simple instrument, simple operation and low cost, and has been widely used in the determination of paracetamol (PCT). For example, the prior art with application publication number CN 108680624A discloses a copper-nickel nanomaterial / multi-walled carbon nanotube composite film modified glassy carbon electrode, prepares a copper-nickel nanomaterial / multi-walled carbon nanotube composite film modified glassy carbon electrode by drop coating method and electrochemical deposition method, and studies the electrochemical behavior of paracetamol (AC) on the modified electrode by cyclic voltammetry.

[0004] However, the existing composite glassy carbon electrodes have the following technical problems: low sensitivity, high detection limit and poor stability in the determination of paracetamol. Summary of the invention

[0005] The present application discloses a bimetallic / carbon nanotube composite modified glassy carbon electrode and its preparation method and application, aiming to solve the technical problems of low sensitivity, high detection limit and poor stability of existing composite electrodes in the determination of paracetamol.

[0006] In order to achieve the above purpose, the technical solution of this application is:

[0007] The first aspect of the present application provides a glassy carbon electrode modified with a bimetallic / carbon nanotube composite, comprising: a glassy carbon electrode substrate and a bimetallic / carbon nanotube composite composited on the glassy carbon electrode substrate;

[0008] The bimetallic / carbon nanotube composite is made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes.

[0009] In combination with the first aspect, preferably, the thickness of the bimetallic / carbon nanotube composite on the glassy carbon electrode substrate is 2-16 μm.

[0010] In combination with the first aspect, preferably, the molar ratio of the nickel-cobalt bimetallic nanoparticles to the multi-walled carbon nanotubes is 1-3:1.

[0011] The second aspect of the present application provides a method for preparing the bimetallic / carbon nanotube composite modified glassy carbon electrode according to the first aspect, the preparation method comprising:

[0012] adding carbon nanotubes into N,N-dimethylformamide to obtain a carbon nanotube suspension;

[0013] Applying the carbon nanotube suspension to the surface of the glassy carbon electrode and drying it to obtain a carbon nanotube-modified glassy carbon electrode;

[0014] The nickel-cobalt bimetallic nanoparticles are deposited on the carbon nanotube-modified glassy carbon electrode by an electrochemical deposition method to obtain the bimetallic / carbon nanotube composite-modified glassy carbon electrode.

[0015] In combination with the second aspect, preferably, the electrochemical deposition method is one of cyclic voltammetry scanning or constant potential deposition.

[0016] The third aspect of the present application provides an electrochemical sensor made of a glassy carbon electrode modified with a bimetallic / carbon nanotube composite as described in the first aspect or a glassy carbon electrode modified with a bimetallic / carbon nanotube composite as prepared by the preparation method described in the second aspect, comprising a working electrode, a counter electrode and a reference electrode;

[0017] The working electrode is a glassy carbon electrode modified by the bimetallic / carbon nanotube composite;

[0018] The counter electrode is a platinum wire electrode;

[0019] The reference electrode is a saturated calomel electrode.

[0020] The fourth aspect of the present application provides the use of the electrochemical sensor described in the third aspect in detecting paracetamol, comprising:

[0021] In a pH = 7.0 PBS solution containing different concentrations of paracetamol, the oxidation peak current value I of the paracetamol solution with different concentrations was measured by differential pulse voltammetry;

[0022] The oxidation peak current value I and the concentration C of the paracetamol solution are plotted into a standard curve;

[0023] The content of paracetamol in the test solution can be obtained by comparing with the standard curve.

[0024] In combination with the fourth aspect, preferably, the linear equation of the standard curve is: I=-1.998C-0.04, R=0.999; wherein the unit of C is μmol / L, and the unit of I is μA.

[0025] In combination with the fourth aspect, preferably, the detection limit of paracetamol is 2 μmol / L.

[0026] Compared with the prior art, the advantages or beneficial effects of the embodiments of the present application include at least:

[0027] The bimetallic / carbon nanotube composite modified glassy carbon electrode provided in the present application is prepared by compounding a bimetallic / carbon nanotube composite made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes on a glassy carbon electrode substrate; on the one hand, the nickel-cobalt bimetallic nanoparticles are uniformly dispersed on the outer wall and cavity of the multi-walled carbon nanotubes, and the composite has no obvious agglomeration phenomenon, has a large specific surface area, and has excellent electrocatalytic activity; on the other hand, the electrochemical sensor made of the glassy carbon electrode modified with the bimetallic / carbon nanotube composite has the advantages of good stability, low detection limit (the embodiment shows that its detection limit is 2 μmol / L), high sensitivity and selectivity in the determination of paracetamol; at the same time, it can realize on-site rapid detection of paracetamol, has the advantages of being easy to carry and simple to operate, and has broad application prospects in drug safety and clinical medicine. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the description of the embodiments. Obviously, the drawings described below are only some embodiments recorded in the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0029] Figure 1 The different modified electrodes provided in the examples of this application have a concentration of 5×10 -4 Cyclic voltammogram of 0.1 mol / L mol / LAC in PBS buffer solution with pH 7.0;

[0030] Among them, (a) Ni-Co bimetallic / carbon nanotube composite modified glassy carbon electrode; (b) Ni-Co bimetallic modified glassy carbon electrode; (c) carbon nanotube composite modified glassy carbon electrode; (d) glassy carbon electrode;

[0031] Figure 2 A graph showing the relationship between AC oxidation current and reduction current at different pH values ​​provided in the examples of the present application;

[0032] Figure 3A graph showing the relationship between the peak current of paracetamol and the square root of the scanning rate provided in an embodiment of the present application;

[0033] Figure 4 This is a graph showing the relationship between the peak current of AC and the concentration of paracetamol provided in the examples of the present application. DETAILED DESCRIPTION

[0034] The technical solutions in the embodiments of the present application will be described clearly and completely below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0035] In the following description of this embodiment, the term "and / or" is used to describe the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, B exists alone, and A and B exist at the same time. A and B can be singular or plural. The character " / " generally indicates that the associated objects before and after are in an "or" relationship.

[0036] In the following description of this embodiment, the term "at least one" refers to one or more, and "plurality" refers to two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all represent: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0037] Those skilled in the art should understand that in the following description of the embodiments of the present application, the order of serial numbers does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0038] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "an" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0039] Those skilled in the art will appreciate that the numerical ranges in the examples of the present application are to be understood as also specifically disclosing each intermediate value between the upper and lower limits of the range. Each smaller range between the intermediate values ​​in any stated value and stated range and any other stated value or intermediate value in the range is also included in the present application. The upper and lower limits of these smaller ranges may be independently included or excluded in the scope.

[0040] Unless otherwise stated, the technical / scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the field described in the present application. Although the present application only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the embodiments or test cases of the present application. All documents mentioned in this specification are generally incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of the present application shall prevail.

[0041] It should be noted that all raw materials and reagents in the examples of the present application were purchased on the market or prepared according to conventional methods well known to those skilled in the art.

[0042] In a first aspect, an embodiment of the present application provides a glassy carbon electrode modified with a bimetallic / carbon nanotube composite, comprising: a glassy carbon electrode substrate and a bimetallic / carbon nanotube composite composited on the glassy carbon electrode substrate;

[0043] The bimetallic / carbon nanotube composite is made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes.

[0044] Among them, on the one hand, the nickel-cobalt bimetallic nanoparticles are uniformly diffused into the multi-walled carbon nanotube cavity, and the composite has no obvious agglomeration phenomenon, has a large specific surface area, and has excellent electrocatalytic activity; on the other hand, the electrochemical sensor made of the glassy carbon electrode modified with the bimetallic / carbon nanotube composite has the advantages of good stability, low detection limit (the embodiment shows that its detection limit is 2 μmol / L), high sensitivity and selectivity in the determination of paracetamol; at the same time, it can realize on-site rapid detection of paracetamol, has the advantages of being easy to carry and simple to operate, and has broad application prospects in drug safety and clinical medicine.

[0045] It should be noted that the bimetallic / carbon nanotube composite used in the present application is made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes. The nickel-cobalt bimetallic nanoparticles are evenly diffused into the inner and outer walls of the carbon nanotube cavity. The essence of electrochemical deposition is electrochemical oxidation-reduction reaction. The reaction system and reaction products of electrochemical deposition will not be contaminated by the reducing agent (or oxidizing agent) and the corresponding oxidation products (or reduction products), and the products are pure and easy to separate.

[0046] In the embodiment of the present application, the thickness of the bimetallic / carbon nanotube composite on the glassy carbon electrode substrate is preferably 2-16 μm; the molar ratio of the nickel-cobalt bimetallic nanoparticles to the multi-walled carbon nanotubes is preferably 1-3: 1. Among them, by controlling the molar ratio of the nickel-cobalt bimetallic nanoparticles to the multi-walled carbon nanotubes and the thickness of the bimetallic / carbon nanotube composite on the glassy carbon electrode substrate, its electrocatalytic activity can be effectively improved, which is conducive to enhancing the detection performance of the composite-modified glassy carbon electrode.

[0047] In a second aspect, the present application provides a method for preparing a glassy carbon electrode modified with a bimetallic / carbon nanotube composite according to the first aspect, the preparation method comprising:

[0048] Adding carbon nanotubes (MWNT) into N,N-dimethylformamide (DMF) to obtain a carbon nanotube suspension;

[0049] Applying the carbon nanotube suspension to the surface of the glassy carbon electrode and drying it to obtain a carbon nanotube-modified glassy carbon electrode;

[0050] The nickel-cobalt bimetallic nanoparticles are deposited on the carbon nanotube-modified glassy carbon electrode by an electrochemical deposition method to obtain the bimetallic / carbon nanotube composite-modified glassy carbon electrode.

[0051] In the embodiment of the present application, the electrochemical deposition method is one of cyclic voltammetry scanning or constant potential deposition. The morphology and loading amount of the nickel-cobalt bimetallic nanoparticles and carbon nanotubes on the glassy carbon electrode can be controlled by controlling the voltage and current.

[0052] In the third aspect, an embodiment of the present application provides an electrochemical sensor made of a glassy carbon electrode modified with a bimetallic / carbon nanotube composite as described in the first aspect or a glassy carbon electrode modified with a bimetallic / carbon nanotube composite prepared by the preparation method described in the second aspect, comprising a working electrode, a counter electrode and a reference electrode, wherein the working electrode is a glassy carbon electrode modified with the bimetallic / carbon nanotube composite; the counter electrode is a platinum wire electrode; and the reference electrode is a saturated calomel electrode.

[0053] It should be noted that the working electrode used in this application is a glassy carbon electrode modified with a bimetallic / carbon nanotube composite, which can undergo a redox reaction with paracetamol and generate a current signal, the magnitude of which is proportional to the concentration of the substance being measured. Therefore, by measuring the current, we can infer the concentration of the substance being measured.

[0054] In a fourth aspect, an embodiment of the present application provides an application of the electrochemical sensor described in the third aspect in detecting paracetamol, including:

[0055] In a pH = 7.0 PBS solution containing different concentrations of paracetamol, the oxidation peak current value I of the paracetamol solution with different concentrations was measured by differential pulse voltammetry;

[0056] The oxidation peak current value I and the concentration C of the paracetamol solution are plotted into a standard curve;

[0057] The content of paracetamol in the test solution can be obtained by comparing with the standard curve.

[0058] In the embodiment of the present application, the linear equation of the standard curve is: I = -1.998C-0.04, R = 0.999; wherein the unit of C is μmol / L, and the unit of I is μA. The detection limit of the paracetamol is preferably 2 μmol / L. The standard curve is plotted by plotting the oxidation peak current value I and the concentration C of the paracetamol solution into a standard curve, and the standard curve equation is fitted, and the content of paracetamol in the test solution is calculated by comparing with the standard curve.

[0059] It should be noted that the bimetallic / carbon nanotube composite modified glassy carbon electrode prepared in the present application has the advantages of good stability, low detection limit, high sensitivity and selectivity in the determination of paracetamol, and has broad application prospects in drug safety and clinical medicine.

[0060] The technical solution of the present application will be further described below in conjunction with specific embodiments.

[0061] Example 1

[0062] This embodiment provides a method for preparing an Al-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode, which specifically includes:

[0063] S101: Add 1 mg MWNT to 1 mL DMF and disperse ultrasonically for 2 hours until a 1 mg / mL black MWNT / DMF suspension is obtained. Take 100 μL of the above 1 mg / mL MWNT / DMF suspension and dilute it to 1 mL with DMF. The glassy carbon electrode (effective diameter 3 mm) was polished on suede with 0.5 and 0.05 μm alumina powder suspensions in turn until it was mirror-like, and then ultrasonically cleaned in anhydrous ethanol and double distilled water for 5 minutes in turn. Use a microinjector to take 5 μL of 0.1 mg / mL WNT / DMF suspension from the treated electrode and drop it on the surface of the glassy carbon electrode, dry it under an infrared lamp, and obtain a multi-walled carbon nanotube modified glassy carbon electrode (MWNT / GCE);

[0064] S102: Multi-walled carbon nanotube modified glassy carbon electrodes were placed in a 1.0×10 -3mol / L cobalt sulfate and nickel sulfate in 0.1mol / L KCl solution, cyclic voltammetry scan 8 times in the range of -1.2 to 1.2V at a scan rate of 100mV / s, rinse the electrode surface with distilled water, dry it and set it aside. Before electrochemical measurement, the modified electrode was first scanned by cyclic voltammetry in 10mL 0.1mol / L PBS buffer (pH=7.0) until the cyclic voltammetry curve was stable. All experiments were carried out at room temperature to obtain A1-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode.

[0065] Example 2

[0066] This embodiment provides a preparation method for an A2-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode. The component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in this embodiment, cyclic voltammetry scans are performed for 18 cycles to obtain an A2-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode.

[0067] Example 3

[0068] This embodiment provides a preparation method for an A3-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode. The component ratio, preparation operation, and process parameters are basically the same as those in Example 1, except that in this embodiment, cyclic voltammetry scanning is performed for 25 cycles to obtain an A3-cobalt nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode.

[0069] In order to verify the electrochemical behavior of the cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode with different thicknesses, the results are shown in Table 1. The three prepared cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrodes were placed in a certain concentration of paracetamol (PBS, 7.0) solution, with a potential range of 0-1.0V, an amplitude of 0.05V, a pulse width of 0.05s, and a pulse period of 0.5s. The prepared cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode was used as the working electrode, the saturated calomel electrode (SCE) was used as the reference electrode, and the platinum column electrode was used as the counter electrode. Differential pulse voltammetry (DPV) was used to determine the effect of different thicknesses of the modified layer on the oxidation peak current of paracetamol (AC).

[0070] Table 1 Electrochemical behavior of Co-Ni bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode

[0071] Serial number thickness Oxidation peak current A1 2μm 0.128V A2 10μm 0.325V A3 16μm 0.267V

[0072] According to Table 1, when the thickness of the bimetallic / carbon nanotube composite on the glassy carbon electrode substrate is 10 μm, the current of its oxidation peak is optimal.

[0073] In order to verify the electrochemical behavior of the prepared Co-Ni bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode, the electrochemical behavior was characterized. Figure 1 As shown. The prepared cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode was placed in paracetamol solutions of different concentrations, with a concentration range of 4-500μmol / L, a potential interval of 0-1.0V, an amplitude of 0.05V, a pulse width of 0.05s, and a pulse period of 0.5s. The prepared cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode was used as the working electrode, a saturated calomel electrode (SCE) was used as the reference electrode, and a platinum wire electrode was used as the counter electrode. Differential pulse voltammetry (DPV) was used to determine the effect of different concentrations of paracetamol (AC) on the oxidation peak current.

[0074] according to Figure 1 It can be seen that paracetamol has a broad oxidation peak at 0.416V on the bare glassy carbon electrode (d), indicating that the electron transfer rate of paracetamol (AC) on the bare electrode is slow; after the cobalt-nickel nanomaterials modified the glassy carbon electrode (b), the redox peak current increased, Epa = 0.354V, Epc = 0.204V, and ΔEp decreased significantly to 150mV, indicating that cobalt-nickel nanoparticles have obvious conductivity for AC; on the multi-walled carbon nanotube modified electrode (c), the redox peak current of AC increased significantly, Epa = 0.368V, Ep c=0.254V, the peak potential difference is reduced to 114mV, indicating that multi-walled carbon nanotubes have good catalytic performance for AC, promoting the transfer speed of electrons on the electrode surface; the cobalt-nickel nanomaterial / multi-walled carbon nanotube composite modified electrode (a) shows the synergistic effect of multi-walled carbon nanotubes and cobalt-nickel nanomaterials, Epa=0.367V, Epc=0.296V, ΔEp is only 71mV, effectively promoting the transfer of electrons on the electrode, and the redox peak current of AC reaches the maximum value, while there is no signal of this redox peak in the blank base solution, that is, PBS=7.0 solution. Therefore, when this modified electrode is used for the detection and analysis of AC, its detection sensitivity can be significantly improved.

[0075] In order to verify the effect of pH on the electrochemical response of paracetamol, the electrochemical behavior of the composite electrode was characterized. The results are shown in Figure 2 shown.

[0076] according to Figure 2 It can be seen that the pH value significantly affects the current response intensity of paracetamol on the modified electrode. As the pH value gradually increases, the oxidation peak current of AC decreases and shows a good linear relationship.

[0077] In order to verify the effect of different scan rates on the electrochemical behavior of PCT, a PBS buffer solution containing 0.5 mmol / L PCT at pH = 7.0 (PBS concentration is 0.1 mol / L, pH 7.0) was used to change the scan rate from 20 mV / s to 600 mV / s. The A2-cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode of Example 2 was used as the working electrode. The cyclic voltammetry method was used for scanning research. The results are shown in FIG. Figure 3 . Scan rate (ak): 20, 50, 80, 120, 150, 180, 200, 300, 400, 500, 600, 700 mV / s.

[0078] according to Figure 3 It can be seen that the redox peak current increases with the increase of scanning speed and shows a good linear relationship. The linear equation of the oxidation peak current is Ipa (μA) = -1.998v 1 / 2 (mV / s)-0.013, the correlation coefficient R is 0.999, and the linear equation of the reduction peak current is Ipc=0.815v 1 / 2 (mV / s)+3.06, and the correlation coefficient R is 0.997, indicating that AC is a diffusion-controlled electrochemical process on the electrode surface.

[0079] In order to verify the linear relationship between the oxidation peak current value I and the concentration C of the paracetamol solution, PCT solutions of different concentrations were prepared with a 0.1 mol / L PBS buffer solution with a pH of 7.0, and the A2-cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode of Example 2 was used as the working electrode. The electrochemical behavior was studied and analyzed by differential pulse voltammetry (DPV). The results are shown in FIG. Figure 4 , the PCT concentrations were: 2, 15, 30, 60, 100, and 200 μmol / L.

[0080] according to Figure 4 It can be seen that as the concentration of PCT solution increases, the oxidation peak current also gradually increases, and the oxidation peak current and concentration show good linearity, the linear equation is I (μA) = -0.1998C (μmol / L) -0.04, the linear correlation coefficient R is 0.999, and the detection limit is 2μmol / L. In this equation, C is the concentration of paracetamol, I is the oxidation peak current value obtained by cyclic voltammetry; the detection limit (LOD) calculated based on the three-fold signal-to-noise ratio is 2μmol / L.

[0081] In order to verify the stability of the cobalt-nickel bimetallic / multi-walled carbon nanotube composite modified glassy carbon electrode, 8 composite modified glassy carbon electrodes were prepared under the same conditions as in Example 2 and subjected to 1.0×10 -3The relative standard deviation (RSD) of the test results was 2.15% when the paracetamol / L was measured respectively; and the RSD was 2.74% when the same paracetamol chemical electrode was used for measurement at 8 different time periods (one test on the first day and one test after one day). Within the allowable range of the relative standard deviation, it is fully demonstrated that the composite chemical electrode prepared by the present application has good stability and reproducibility, and can be used for the detection of paracetamol content.

[0082] Therefore, the bimetallic / carbon nanotube composite modified glassy carbon electrode provided in the present application is prepared by compounding the bimetallic / carbon nanotube composite made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes on a glassy carbon electrode substrate. It has excellent electrocatalytic activity, and has the advantages of good stability, low detection limit (the embodiment shows that its detection limit is 2 μmol / L), high sensitivity and selectivity in the determination of paracetamol; at the same time, it can realize on-site rapid detection of paracetamol, has the advantages of being easy to carry and simple to operate, and has broad application prospects in drug safety and clinical medicine.

[0083] The various embodiments in this specification are described in a progressive manner, and the same or similar parts between the various embodiments can be referenced to each other, and each embodiment focuses on the differences from other embodiments.

[0084] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit the present application. Although the present application has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions recorded in the aforementioned embodiments may still be modified, or some or all of the technical features therein may be replaced by equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the present application.

Claims

1. A glassy carbon electrode modified with a bimetallic / carbon nanotube composite, characterized in that: include: A glassy carbon electrode substrate and a bimetallic / carbon nanotube composite compounded on the glassy carbon electrode substrate; The bimetallic / carbon nanotube composite is made of nickel-cobalt bimetallic nanoparticles and multi-walled carbon nanotubes.

2. The bimetallic / carbon nanotube composite modified glassy carbon electrode according to claim 1, characterized in that: The thickness of the bimetal / carbon nanotube composite on the glassy carbon electrode substrate is 2-16 μm.

3. The bimetallic / carbon nanotube composite modified glassy carbon electrode according to claim 1, characterized in that: The molar ratio of the nickel-cobalt bimetallic nanoparticles to the multi-walled carbon nanotubes is 1-3:

1.

4. A method for preparing a bimetallic / carbon nanotube composite modified glassy carbon electrode according to any one of claims 1 to 3, characterized in that: The preparation method comprises: adding carbon nanotubes into N,N-dimethylformamide to obtain a carbon nanotube suspension; Applying the carbon nanotube suspension to the surface of the glassy carbon electrode and drying it to obtain a carbon nanotube-modified glassy carbon electrode; The nickel-cobalt bimetallic nanoparticles are deposited on the carbon nanotube-modified glassy carbon electrode by an electrochemical deposition method to obtain the bimetallic / carbon nanotube composite-modified glassy carbon electrode.

5. The method for preparing a bimetallic / carbon nanotube composite modified glassy carbon electrode according to claim 4, characterized in that: The electrochemical deposition method is one of cyclic voltammetry scanning and constant potential deposition.

6. An electrochemical sensor made of a glassy carbon electrode modified with a bimetallic / carbon nanotube composite as claimed in any one of claims 1 to 3 or a glassy carbon electrode modified with a bimetallic / carbon nanotube composite as prepared by the preparation method as claimed in any one of claims 4 to 5, characterized in that: It includes working electrode, counter electrode and reference electrode; The working electrode is a glassy carbon electrode modified by the bimetallic / carbon nanotube composite; The counter electrode is a platinum wire electrode; The reference electrode is a saturated calomel electrode.

7. Use of the electrochemical sensor according to claim 6 in detecting paracetamol, characterized in that: include: In a pH = 7.0 PBS solution containing different concentrations of paracetamol, the oxidation peak current value I of the paracetamol solution with different concentrations was measured by differential pulse voltammetry; The oxidation peak current value I and the concentration C of the paracetamol solution are plotted into a standard curve; The content of paracetamol in the test solution can be obtained by comparing with the standard curve.

8. Use of the electrochemical sensor according to claim 6 in detecting paracetamol, characterized in that: The linear equation of the standard curve is: I=-1.998C-0.04, R=0.999; wherein the unit of C is μmol / L, and the unit of I is μA.

9. Use of the electrochemical sensor according to claim 6 in detecting paracetamol, characterized in that: The detection limit of paracetamol is 2 μmol / L.

Citation Information

Patent Citations

  • Glassy carbon electrode modified with copper-nickel nanomaterial / multiwalled carbon nanotube composite film, and preparation method and application thereof

    CN108680624A

Cited By

  • Construction method and application of electrochemical sensor based on nitrogen-doped carbon-cobalt-nickel diatomic catalyst

    CN120651937A